THE IMPACT OF FOREIGN RELATION ON ECONOMIC POLICY IN AFRICA - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Foreign refers to the conduct of human affairs by peaceful means, employing techniques of persuasion and negotiation (Barnett and Duvall, 2010). It usually refers to international diplomacy, the conduct of international relations through the intercession of professional diplomats with regard to issues of peace-making, trade, war, economics, culture, environment and human relations (Berridge, 2005). Diplomacy is typically carried out by government officials, who use bargaining, negotiation, and other peaceful means to negotiate treaties, trade policies, and other international agreements, including agreements to prevent, limit, manage, or settle conflicts (Claude, 2012).